2013
DOI: 10.1155/2013/312348
|View full text |Cite
|
Sign up to set email alerts
|

Hospital-Acquired Infection Underlies Poor Functional Outcome in Patients with Prolonged Length of Stay

Abstract: IntroductionProlonged length of stay (pLOS) following ischemic stroke inflates cost, increases risk for hospital-acquired complications, and has been associated with worse prognosis.MethodsAcute ischemic stroke patients admitted between July 2008 and December 2010 were retrospectively analyzed for pLOS, defined as a patient stable for discharge hospitalized for an additional ≥24 hours.ResultsOf 274 patients included, 106 (38.7%) had pLOS (median age 65 years, 60.6% female, 69.0% black). Patients with pLOS had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 23 publications
1
18
1
1
Order By: Relevance
“…Infection is considered a confounding variable because previous studies in Taiwan, the United States, Denmark, and the United Kingdom mentioned infection affecting the length of stay in acute ischemic stroke patients. 11,19 The results of this study are in accordance with previous studies in the United States. Research in the United States found that ischemic stroke patients with gastrointestinal bleeding had a longer average length of stay (11 days) than without gastointestinal bleeding (5 days) with a 2.3 times longer risk of treatment.…”
Section: Relationship To Gastrointestinal Bleeding With Length Of Staysupporting
confidence: 92%
“…Infection is considered a confounding variable because previous studies in Taiwan, the United States, Denmark, and the United Kingdom mentioned infection affecting the length of stay in acute ischemic stroke patients. 11,19 The results of this study are in accordance with previous studies in the United States. Research in the United States found that ischemic stroke patients with gastrointestinal bleeding had a longer average length of stay (11 days) than without gastointestinal bleeding (5 days) with a 2.3 times longer risk of treatment.…”
Section: Relationship To Gastrointestinal Bleeding With Length Of Staysupporting
confidence: 92%
“…Sepsis and pneumonia are common, and highly morbid, infectious complications in stroke patients (1). The development of post-stroke infection leads to multiple poor outcomes including neurologic deterioration (2), prolonged hospital length of stay (3), poor functional outcome, and death (4). The high clinical impact and limited effective strategies for prevention or treatment of post-stroke infection indicate the need for further investigation into underlying mechanisms and potential therapeutic options.…”
Section: Introductionmentioning
confidence: 99%
“…This new information contrasts with AC studies, where the presence of SUTI was predictive of rehabilitation care in a SNF, a level of care suggestive of lower functional status and worse outcomes [12,15]. The obviated impact of UTI on community discharge is due to the standard protocol of collecting a urine sample within 24 hours of rehabilitation admission.…”
Section: Discussionmentioning
confidence: 77%
“…HAIs in the acute stroke patient have been associated with poor outcomes due to both prolonged hospitalization for antibiotic treatment and suboptimal participation in acute rehabilitation [8][9][10]. The most prevalent, SUTI (symptomatic urinary tract infection), accounts for over 21% of HAI incidence; studies have found that UTI [urinary tract infection] is one of the most frequent complications of stroke, with rates of 1 to 24% within the first month [11][12][13]. Sien Ng et al [14] noted that higher discharge FIM score was associated the absence of HAI's.…”
mentioning
confidence: 99%